Functional Role of Native and Invasive Filter-Feeders, and the Effect of Parasites: Learning from Hypersaline Ecosystems - Sánchez, Marta I.; Paredes, Irene; Lebouvier, Marion; Green, Andy J. (PLOS ONE, 2016)
Filter-feeding organisms are often keystone species with a major influence on the dynamics of aquatic ecosystems. Studies of filtering rates in such taxa are therefore vital in order to understand ecosystem functioning and the impact of natural and anthropogenic stressors such as parasites, climate warming and invasive species. Brine shrimps Artemia spp. are the dominant grazers in hypersaline systems and are a good example of such keystone taxa. Hypersaline ecosystems are relatively simplified environments compared with much more complex freshwater and marine ecosystems, making them suitable model systems to address these questions. The aim of this study was to compare feeding rates at different salinities and temperatures between clonal A. parthenogenetica (native to Eurasia and Africa) and the invasive American brine shrimp A. franciscana, which is excluding native Artemia from many localities. We considered how differences observed in laboratory experiments upscale at the ecosystem level across both spatial and temporal scales (as indicated by chlorophyll-a concentration and turbidity). In laboratory experiments, feeding rates increased at higher temperatures and salinities in both Artemia species and sexes, whilst A. franciscana consistently fed at higher rates. A field study of temporal dynamics revealed significantly higher concentrations of chlorophyll-a in sites occupied by A. parthenogenetica, supporting our experimental findings. Artemia parthenogenetica density and biomass were negatively correlated with chlorophyll-a concentration at the spatial scale. We also tested the effect of cestode parasites, which are highly prevalent in native Artemia but much rarer in the invasive species. The cestodes Flamingolepis liguloides and Anomotaenia tringae decreased feeding rates in native Artemia, whilst Confluaria podicipina had no significant effect. Total parasite prevalence was positively correlated with turbidity. Overall, parasites are likely to reduce feeding rates in the field, and their negative impact on host fecundity is likely to exacerbate the difference between grazing rates of native and alien Artemia populations at the ecosystem level. The results of this study provide evidence for the first time that the replacement of native Artemia by A. franciscana may have major consequences for the functioning of hypersaline ecosystems. The strong effect of parasites on feeding rate underlines the importance of taking parasites into account in order to improve our understanding of the functioning of aquatic ecosystems.